Growth pathways of exotic Cu@Au core@shell structures: the key role of misfit strain. Issue 5 (17th January 2023) - El koraychy, El yakout; Ferrando, Riccardo
Abstract : The CuAu system is characterized by a large lattice mismatch which causes a misfit strain in its core@shell architectures. Abstract : The CuAu system is characterized by a large lattice mismatch which causes a misfit strain in its core@shell architectures. Here we simulate the formation of Cu@Au core@shell nanoparticles by Au deposition on a preformed seed, and we study the effect of the shape and composition of the starting seed on the growth pathway. Three geometric shapes of the starting seed are considered: truncated octahedra, decahedra and icosahedra. For each shape, we consider two compositions, pure Cu and CuAu, at equicomposition and intermixed chemical ordering. Our results show that the shape and composition of the seed have significant effects on the growth pathways of Cu@Au core@shell nanoparticles. When starting with icosahedral seeds, the growing structure stays in that motif always. When starting with truncated octahedral and decahedral seeds, we have observed that there is a clear difference between the pure and intermixed seeds. For pure seeds, the growth often leads to exotic structures that are obtained after some structural transformations. For mixed seeds, the growth leads to quite regular structures resembling those obtained for pure metals. These growth pathways originate from strain relaxation mechanisms, which are rationalized by calculating the atomic level stress.